2021
DOI: 10.3390/f12010056
|View full text |Cite
|
Sign up to set email alerts
|

How Do Plants Respond Biochemically to Fire? The Role of Photosynthetic Pigments and Secondary Metabolites in the Post-Fire Resprouting Response

Abstract: Resprouting is one of the main regeneration strategies in woody plants that allows post-fire vegetation recovery. However, the stress produced by fires promotes the biosynthesis of compounds which could affect the post-fire resprouting, and this approach has been poorly evaluated in fire ecology. In this study, we evaluate the changes in the concentration of chlorophylls, carotenoids, phenolic compounds, and tannins as a result of experimental burns (EB). We asked whether this biochemical response to fire coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
7
1
1
Order By: Relevance
“…These results could be related to higher physiological stability of the seedlings of the SM treatment compared to other treatments. Photosynthetic pigments could be considered an indicator of the stability of plant regulatory functions [18]. Although previous studies have reported that the effect of AM fungi improved chlorophyll content in leaves under drought or salt stress conditions [19], the mycorrhizas did not induce a clear biochemical response in this study.…”
Section: Biochemical Responsecontrasting
confidence: 69%
“…These results could be related to higher physiological stability of the seedlings of the SM treatment compared to other treatments. Photosynthetic pigments could be considered an indicator of the stability of plant regulatory functions [18]. Although previous studies have reported that the effect of AM fungi improved chlorophyll content in leaves under drought or salt stress conditions [19], the mycorrhizas did not induce a clear biochemical response in this study.…”
Section: Biochemical Responsecontrasting
confidence: 69%
“…The absence of chemical defense variability in plants under stress caused by the environment or other organisms would imply a possible population reduction. Therefore, high chemical diversity allows plants to respond to various environmental conditions, as Santacruz-García et al (2021) reported in a recent study on six woody species from the Chaco, including a Rhamnaceae family species with wide variations in total phenolic and tannin concentrations. Our results presented a high standard deviation value, suggesting a high intrapopulation variability, which can be attributed to adaptation, according to Valares (2011).…”
Section: Discussionmentioning
confidence: 94%
“…Contrariamente en el totoral sin quema las concentraciones fueron significativamente superiores en el rebrote (8,69 %) y significativamente menores hacia la madurez (5,96 %) (Figura 2d). Aunque no hubo un efecto claro por el uso del fuego, sí se evidencia un relativo incremento en el totoral con quema en la etapa de crecimiento, similar a lo hallado por Santacruz et al (2021) quienes explican que el incremento en los compuestos lipídicos por efecto de la quema, entre los que incluyen altos niveles de fenoles, promueven su regeneración y crecimiento, como una respuesta funcional al fuego.…”
Section: Resultados Y Discusiónunclassified